Collaboration and Student Motivation Achievement In Physics Learning - Tambunan, Maranatha; Sihite, Koster (Universitas Negeri Medan, 2020)
Teaching and learning activities that tend to be monotonous and passive lead to low student interest and student achievement. Therefore, this study aims to determine fellow collaboration and achievement of student motivation in learning physics. This research is applied with a learning model in six phases that can increase collaboration, motivation and student achievement, namely choosing topics, cooperative planning, implementation, analysis and synthesis, presentation, evaluation. This type of research is a quasi experiment. The instrument used was a student's conceptual knowledge test in the form of a description of 8 items and student activity sheets namely experimental activities. The results showed that collaboration with good students will affect the achievement of student motivation in learning physics.